Swipe Right?: Experimental Analyses of App-Based Dating in the Age of Criminal Stigma. Issue 4 (8th August 2022) - Evans, Douglas N.; Blount-Hill, Kwan Lamar
ABSTRACT: Stigma associated with prior incarceration could make dating difficult. To test this in online dating, an experimental audit used constructed dating app profiles of Black, Latinx, and White males and females. Experimental and control profiles were identical with the exception of a parole disclosure statement in bios of experimental profiles. Surprisingly, the White female profile disclosing parole was the only one to match with significantly fewer users. We analyzed the racial congruence of matches and found that White parole disclosing profiles were more likely to attract White users and Black and Latinx profiles attracted more heterogeneous users regardless of parole disclosure. The interaction between racial and criminal stigma and implications for relationship prospects among the formerly incarcerated are considered. Although the timing of criminal history disclosure matters, criminal stigma is unique in app-based dating, having more negative effects for Whites, which differs from other social domains.